Impact of Motivation and Recognition on Employeeas Performance: A Study on Public and Private Sector Banks in Punjab and Haryana (Global Journal of Management and Business Research, 2015)
Correlation is significant at the 0.01 level (2-tailed).
Keywords: motivation; recognition; employee performance; public sectors banks; punjab